Sepsis: Issues of Terminology, Classification and Epidemiology - O. A. Noskova; E. V. Anganova; G. V. Gvak; E. D. Savilov (Эпидемиология и вакцинопрофилактика, 2018)
Despite the clinical epidemiological, social and economic significance, the problems of sepsis terminology and classification till now are discussed in many respects. Data on sepsisology development as clinical discipline are represented, problems of sepsis terminology evolution, its classification, the matter of septic states are discussed. The importance of formulation of the "sepsis" concept for development of diagnostic criteria, treatment principles and prevention is shown. Special attention is directed to epidemiological manifestations of this pathological syndrome.